2019
DOI: 10.1038/s41379-019-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Oncoproteomic and gene expression analyses identify prognostic biomarkers for second primary malignancy in patients with head and neck squamous cell carcinoma

Abstract: Patients with head and neck squamous cell carcinoma are at increased risk of developing a second primary malignancy, which is associated with poor prognosis and early death. To help improve clinical outcome, we aimed to identify biomarkers for second primary malignancy risk prediction using the routinely obtained formalin-fixed paraffin-embedded tissues of the index head and neck cancer. Liquid chromatography-tandem mass spectrometry was initially performed for candidate biomarker discovery in 16 pairs of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The 5 years survival rate is under 65% due mostly to the late diagnosis in the absence of early symptoms [3]. About 90% of all head and neck cancers are squamous cell carcinomas (HNSCC) [4]. Apart of surgery the main treatment protocol for HNSCC is radiotherapy (RT) combined with chemotherapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…The 5 years survival rate is under 65% due mostly to the late diagnosis in the absence of early symptoms [3]. About 90% of all head and neck cancers are squamous cell carcinomas (HNSCC) [4]. Apart of surgery the main treatment protocol for HNSCC is radiotherapy (RT) combined with chemotherapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism (in terms of genomics and proteomics) of SPTs in patients with H&N cancer is crucial and has been well analyzed and reported. For example, Bunbanjerdsuk et al have analyzed the oncoproteomics and gene expression and reported ITPR3, KMT2D , and EMILIN1 as prognostic factors in SPT for patients with H&N cancer (80). da Silva et al have reported that epithelial-mesenchymal transition markers such as E-cadherin and beta-catenin , exhibit a significant prognostic impact in multiple primary oral SCC cases (81).…”
Section: Discussionmentioning
confidence: 99%
“…Among them that have been functionally characterized, several has been linked to malignant progression [13][14] . Notably, many genes have key roles for diagnostic accuracy and predicting the prognosis [15][16] .…”
Section: Introductionmentioning
confidence: 99%